Racial/Ethnic Differences in Knowledge, Attitudes, and Beliefs About COVID-19 Among Adults in the United States - Reiter, Paul L.; Katz, Mira L. (Frontiers in Public Health, 2021)
Background. Knowledge, attitudes, and beliefs are key determinants of engaging in health behaviors, likely including vaccination and other mitigation behaviors against coronavirus disease 2019 (COVID-19). However, little is known about how these cognitive outcomes differ across racial/ethnic groups. Methods. We conducted an online survey of adults ages 18 and older in the United States (n=2,006) in May 2020, about two months after COVID-19 was declared a pandemic. Multivariable regression models examined differences in knowledge, attitudes, and beliefs about COVID-19 across racial/ethnic groups (non-Latinx white, non-Latinx black, non-Latinx of another race, or Latinx). Results. Knowledge tended to be lower among non-Latinx blacks and Latinx participants compared to non-Latinx whites. For example, fewer non-Latinx blacks responded correctly that COVID-19 is not caused by the same virus that causes influenza (adjusted OR=0.66, 95% CI: 0.49–0.90), and Latinx participants were less likely to respond correctly that people with COVID-19 do not always show symptoms of being sick (adjusted OR=0.63, 95% CI: 0.45–0.87). For beliefs and attitudes, non-Latinx blacks (β=-0.09) and non-Latinx participants of another race (β=-0.05) reported lower perceived likelihood of getting COVID-19 in the future compared to non-Latinx whites, while Latinx participants reported greater perceived stigma of COVID-19 (β = 0.08) (all p<0.05). Conclusions. Several differences in cognitive outcomes about COVID-19 exist across racial/ethnic groups, including gaps in knowledge and varied beliefs and attitudes. Results identify modifiable targets for public health programs promoting vaccination and other mitigation behaviors against COVID-19.